Expenditure responses, policy interventions and heterogeneous welfare effects in Hungary during the 2000s - Zsombor Cseres-Gergely; György Molnár; Tibor Szabó (Hungarian Academy of Sciences, Institute of Economics, 2017)
VAT rates have changed multiple times and to a relatively great extent in Hungary during the past years. We use the resulting price changes in estimating the price- and income-elasticity of households' expenditures. As a novelty, we introduce an interaction term in estimating the demand system and show that the own price elasticity of food is increasing with increasing production for own consumption. Based on the estimation results, we compute the average welfare effect of the changes and describe also its heterogeneity within the population. We find that the VAT-reforms in 2006 and 2009 have both decreased the welfare of those in the first income quintile. We also look at the welfare effect of multiple hypothetic reforms such as the decrease of the VAT rate of food and a decrease of utility prices as well as a subsidy to production for own consumption. We find that the best targeted measure is an income-transfer to the low-income unemployed either directly or through participation in the public works scheme.
Keywords: D12; H20; H31; 330; QUAIDS model; household expenditures; consumer behaviour; compensating variation; simulation; welfare effect; production for own consumption